The Role of Exercise in Improving Sleep Quality Across Sleep Disorders: A Comprehensive Review - Paduch-Jakubczyk, Wiktoria; Dubińska, Michalina; Bilska, Wiktoria; Ciułek, Urszula; Dobosz, Anna; Zduńczyk, Wiktoria; Żydek, Ada (Quality in Sport, 2024)
Introduction and Objective: Sleep disturbances are increasingly common in the general population, posing significant public health challenges and economic burdens. Traditional treatments frequently fall short, leading to increased interest in physical activity as an alternative approach. This review aims to evaluate the efficacy of exercise in improving sleep quality across various conditions, including obstructive sleep apnea (OSA), insomnia, Parkinson’s Disease (PD), depression and the perimenopausal period. Review and Methods: The review draws from studies, including randomized controlled trials and meta-analyses, sourced via Google Scholar and PubMed. State of Knowledge: Research highlights the significant public health impact of sleep disturbances. Studies suggest that regular exercise can improve sleep quality across conditions like OSA, PD, depression, and menopause. Traditional treatments, such as CPAP, psychotherapy, and medications, often have limitations. As a result, there is growing interest in using physical activity as alternative therapy or a complementary approach to enhance these existing options. Conclusions: Exercise shows promise as a non-pharmacological intervention for sleep disorders, offering potential benefits for various conditions. Further research is needed to refine exercise protocols and understand its mechanisms. Integrating physical activity into treatment plans could enhance sleep quality and health outcomes alongside existing therapies.